NIHILISTINIS TEISINGUMAS SU RICOEURU IR DERRIDA. - Šerpytytė, Rita (Problems / Problemos, 2014)
This article aims to radicalize the problem of justice by proposing a theoretical hypothesis of justice, traceable only as a negative and Nihilistic experience par excellence. While drawing on Ricoeur's and Den-ida's works, the "nature" of justice is exposed in the twofold perspective - as justice appearing within or beyond law. The author shows how Derrida's concept of justice emerges as "originary lack", as Diff&ance, as an interruption between justice as law and injustice. By deploying the conclusions of Deconstruction as well as Heidegger's analysis of diKq, the nihilistic take is exercised in order to verify Ricoeur's formalist interpretation of this subject. The instance of "impersonal point of view" turns out to be essential in giving a background of the formalist understanding of justice. Since this instance is conceived as an open, self-sufficient and incomplete form, through which the ambivalence and ambiguity of human being is disclosed as well as an opening to the Otherness - both universal and singular - is performed, Ricoeur's position can become a subject of nihilistic interpretation, proposing the understanding of"impersonal point of view" as "moral gap", as a crack injustice of law.